Ultrasound common carotid artery video simulation and motion analysis - Solomou, Rafaella; Loizou, Christos P.; Kasparis, Takis (My University, 2016)
The carotid artery wall motion characteristics from ultrasound videos may provide useful information regarding healthy, asymptomatic or symptomatic subjects as well as aid in the development and validation of motion analysis algorithms. This still remains a challenging task, as actual motion characteristics and indices are not directly available. In the present work we propose a methodology for generating simulated common carotid artery (CCA) ultrasound videos, which consists of the following steps: i) Generate the first frame of the CCA video using an artificial carotid image, ii) Generate the consecutive video frames by applying motion in the axial and radial directions, iii) Apply random speckle noise in each consecutive video frame, iv) Generate the systolic and diastolic frames of the entire cardiac cycle and v) Extract measurements for evaluating the CCA motion characteristics. A total of 120 frames were generated for each simulated video covering three cardiac cycles. Error measurements are presented for evaluating the simulation result. The proposed simulation procedure is simple and not computationally efficient and can thus be used widely in assessing the performance of different motion estimation and analysis algorithms.
Keywords: Artificial carotid video; Common carotid artery; Motion simulation; Ultrasound video